Managing institutional risk for Veterinary Services - Solomos, G.; Randolph, Thomas F. (World Organisation for Animal Health, 2021)
The use of institutional risk assessment and management, considered best practice in management sciences, is not systematically used across public Veterinary Services. Chief Veterinary Officers and their teams often lack exposure to or training in the application of this type of institutional risk assessment. This paper describes the essential elements of institutional risk assessment and how it might be applied within the context of Veterinary Services.